A vegan dietary pattern is associated with high prevalence of inadequate protein intake in older adults; a simulation study - Jos W. Borkent; Pol Grootswagers; Joost Linschooten; Annet J.C. Roodenburg; Marga Ocké; Marian A.E. de van der Schueren (The Journal of Nutrition, Health and Aging)
Background: A more sustainable diet with fewer animal-based products has a lower ecological impact but might lead to a lower protein quantity and quality. The extent to which shifting to more plant-based diets impacts the adequacy of protein intake in older adults needs to be studied. Objectives: We simulated how a transition towards a more plant-based diet (flexitarian, pescetarian, vegetarian, or vegan) affects protein availability in the diets of older adults. Setting: Community. Participants: Data from the Dutch National Food Consumption Survey 2019–2021 of community-dwelling older adults (n = 607) was used. Measurements: Food consumption data was collected via two 24-h dietary recalls per participant. Protein availability was expressed as total protein, digestible protein, and utilizable protein (based on digestibility corrected amino acid score) intake. The percentage below estimated average requirements (EAR) for utilizable protein was assessed using an adjusted EAR. Results: Compared to the original diet (∼62% animal-based), utilizable protein intake decreased by about 5% in the flexitarian, pescetarian and vegetarian scenarios. In the vegan scenario, both total protein intake and utilizable protein were lower, leading to nearly 35% less utilizable protein compared to the original diet. In the original diet, the protein intake of 7.5% of men and 11.1% of women did not meet the EAR. This slightly increased in the flexitarian, pescetarian, and vegetarian scenarios. In the vegan scenario, approximately 60% had a protein intake below EAR. Conclusions: Replacing animal-based protein sources with plant-based food products in older adults reduces both protein quantity and quality, albeit minimally in non-vegan plant-rich diets. In a vegan scenario, the risk of an inadequate protein intake is imminent.